2020
DOI: 10.1101/2020.11.05.368076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of autosomal cis expression quantitative trait methylation (cis eQTMs) in children’s blood

Abstract: Background: The identification of expression quantitative trait methylation (eQTMs), defined as correlations between gene expression and DNA methylation levels, might help the biological interpretation of epigenome-wide association studies (EWAS). We aimed to identify autosomal cis-eQTMs in child blood, using data from 832 children of the Human Early Life Exposome (HELIX) project. Methods: Blood DNA methylation and gene expression were measured with the Illumina 450K and the Affymetrix HTA v2 arrays, respectiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 78 publications
(234 reference statements)
3
7
1
Order By: Relevance
“…Only 16% (3,861 out of 23,862 eQTMs) of the Ruiz-Arenas et al 3 eQTMs were also significant in our study, but 97% (3,731 of the 3,861) had consistent effect direction. The small overlap of eQTMs between our study and Ruiz-Arenas et al 3…”
Section: Meta-analysis Identifies Eqtms That Are Robust Across Different Tissuescontrasting
confidence: 68%
See 3 more Smart Citations
“…Only 16% (3,861 out of 23,862 eQTMs) of the Ruiz-Arenas et al 3 eQTMs were also significant in our study, but 97% (3,731 of the 3,861) had consistent effect direction. The small overlap of eQTMs between our study and Ruiz-Arenas et al 3…”
Section: Meta-analysis Identifies Eqtms That Are Robust Across Different Tissuescontrasting
confidence: 68%
“…Ruiz-Arenas et al also observed. 3 We further identified eQTM associations for 2,243 additional genes compared to Bonder et al 4 and 5,872 additional genes compared to Ruiz-Arenas et al 3 As expected, the majority of the eQTM genes (n=4,176; 67%) were negatively correlated with the nearby CpG sites (Table 1). We tested whether this directionality was consistent among different tissues by replicating the discovered eQTMs in each of the three tissues separately and observed that over 98% of the eQTMs identified significantly in both the meta-analysis and in each tissue shared the same direction (Figure 1).…”
Section: Could Reflect Differences Between Adult and Child Cohorts Asmentioning
confidence: 54%
See 2 more Smart Citations
“…We did conduct an analysis of functionality using the Human Early Life Exposome expression quantitative trait (eQTM) loci database 55 however, none of the ve CpG sites from the primary or secondary meta-analyses were identi ed as an eQTM. Further functional analyses are necessary to better de ne the relationship between DNA methylation of our sign cant loci and gene expression.…”
Section: Follow-up Analyses (Dmr Becon Mqtl Eqtm)mentioning
confidence: 99%